2016
DOI: 10.1101/089342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic transmission disequilibrium confirms that common and rare variation act additively to create risk for autism spectrum disorders

Abstract: Autism spectrum disorder (ASD) risk is influenced by common polygenic and de novo variation.We aimed to clarify the influence of polygenic risk for ASDs and to identify subgroups of ASD cases, including those with strong acting de novo variants, in which polygenic risk is relevant.Using a novel approach called the polygenic transmission disequilibrium test, and data from 6,454 families with a child with ASD, we show that polygenic risk for ASDs, schizophrenia, and greater educational attainment is over transmi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
243
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(270 citation statements)
references
References 37 publications
22
243
3
2
Order By: Relevance
“…42 Although this marker is intronic, it is in linkage disequilibrium with a number of other markers that span a gene-rich region. 44 However, single nucleotide polymorphism heritability is higher among those cases without intellectual disability, supporting the observation that de novo and sporadic variants are more frequently observed among cases of ASD with intellectual disability. Furthermore, evidence of heterogeneity of association across phenotypic subgroups was observed; for example, the higher functioning subgroup showed an excess of alleles that overlapped with educational attainment.…”
Section: Common Mutations In Asdmentioning
confidence: 63%
“…42 Although this marker is intronic, it is in linkage disequilibrium with a number of other markers that span a gene-rich region. 44 However, single nucleotide polymorphism heritability is higher among those cases without intellectual disability, supporting the observation that de novo and sporadic variants are more frequently observed among cases of ASD with intellectual disability. Furthermore, evidence of heterogeneity of association across phenotypic subgroups was observed; for example, the higher functioning subgroup showed an excess of alleles that overlapped with educational attainment.…”
Section: Common Mutations In Asdmentioning
confidence: 63%
“…Somatic mutations could also modify brain functions and dysfunctions in addition to the individual's germline genomic features. Rare and common germline variants additively contribute to autism spectrum disorder (ASD) . Somatic mutations would also contribute additively to brain function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analyses soon provided direct evidence for this in the case of schizophrenia (Purcell et al, 2009) and showed that, together, common variants can explain much of the expected heritability (Yang et al, 2010). While traits vary greatly in terms of both the importance of the largest-effect common variants and of higher-penetrance rare variants (Loh et al, 2015, Shi et al, 2016, Sullivan et al, 2017), it is now clear that polygenic effects are important across a wide variety of traits (Shi et al, 2016, Weiner et al, 2016). …”
Section: Distribution Of Gwas Signals Across the Genomementioning
confidence: 99%
“…Indeed, human geneticists expected that even complex traits would be driven by a handful of moderate-effect loci–thus giving rise to large numbers of mapping studies that were, in retrospect, greatly underpowered. For example, an elegant 1999 analysis of allele-sharing in autistic siblings concluded from the lack of significant hits that there must be “a large number of loci (perhaps ≥15)”–this prediction was strikingly high at the time, but seems quaintly low now (Risch et al, 1999, Weiner et al, 2016). …”
mentioning
confidence: 99%